REKONSTRUKSI PEMBELAJARAN MATEMATIKA SD BERBASIS STEAM SEBAGAI STRATEGI PENGUATAN LITERASI NUMERASI DAN KETERAMPILAN ABAD KE-21 - Isa, Muhammad; Saila, Nurul; Handayani, Linda; Elianti, Elianti; Erlina, Leni (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
The transformation of education in the 21st century requires mathematics learning that is not only oriented toward the mastery of concepts but also toward strengthening numeracy literacy and developing 21st-century skills. One approach considered capable of addressing these demands is the STEAM (Science, Technology, Engineering, Art, and Mathematics) approach, which integrates multiple disciplines within contextual and collaborative learning. This study aims to analyze the contribution of the STEAM approach in elementary school mathematics learning toward strengthening numeracy literacy and 21st-century skills, as well as to formulate a conceptual framework for reconstructing STEAM-based mathematics learning. The study employed a Systematic Literature Review (SLR) method with a qualitative approach. Data were obtained from the Google Scholar, SINTA, and Scopus databases using keywords relevant to STEAM-based mathematics learning. The article selection process was conducted through the stages of identification, screening, and comprehensive content review. The initial search identified 56 articles, which were subsequently narrowed down to 33 articles based on the relevance of their titles and abstracts, and finally 16 articles met the inclusion criteria and were analyzed further. Data analysis was carried out using content analysis and narrative synthesis to identify patterns in the research findings. The results of the review indicate that the STEAM approach contributes positively to improving numeracy literacy and developing 21st-century skills, including critical thinking, creativity, collaboration, and communication. Furthermore, the integration of STEAM with active learning models such as Project-Based Learning and Problem-Based Learning can create more meaningful and contextual mathematics learning experiences in elementary schools